Tinnitus Suppression After Auditory Brainstem Implantation in Patients With Neurofibromatosis Type-2. Issue 1 (January 2017) - Roberts, Daniel S.; Otto, Steve; Chen, Brian; Peng, Kevin A.; Schwartz, Marc S.; Brackmann, Derald E.; House, John W.
Abstract : Objective: To evaluate whether an auditory brainstem implant (ABI) can impact levels of tinnitus in neurofibromatosis type-2 (NF2) patients who have undergone translabyrinthine craniotomy for vestibular schwannoma (VS) removal and to evaluate the burden of tinnitus in these patients. Study Design: A retrospective case series and patient survey. Setting: Tertiary neurotologic referral center. Patients: NF2 patients who underwent translabyrinthine removal of VS and ABI placement between 1994 and 2015. Interventions: A survey, retrospective review and two validated tinnitus handicap questionnaires (tinnitus handicap inventory [THI] and tinnitus visual analogue scale [VAS]) were used to characterize the degree of tinnitus in NF2 patients and whether an ABI can alter tinnitus levels. Main Outcome Measures(s): Survey results, THI and VAS scores. Results: One hundred twelve ABI users were contacted and 43 patients (38.3)% responded to our survey. Tinnitus was reported in 83.7% of patients. The THI score for responders was 17.8 ± 20.5 standard deviation (SD). For survey participants, the ABI reduced tinnitus levels (mean VAS: Off = 3.5; On 1-h = 2.1; p = 0.048). For patients who subjectively reported that the ABI reduced tinnitus loudness, tinnitus levels were immediately reduced on ABI activation and after 1 hour of use (mean VAS: Off = 4.8; On = 2.4; On 1-h = 1.8; p < 0.01). Suppression did not continue after the device was turned off. Audiological performance with the ABI did not correlate with tinnitus suppression. Conclusion: NF2 patients who have undergone removal of VS have a significant tinnitus handicap and benefit from tinnitus suppression through utilization of an ABI possibly through masking or electrical stimulation of the auditory brainstem.